Antecedents of CSR Disclosure in Manufacturing Companies in Indonesia - Ivana Oktarina Sopacua (The Indonesian Accounting Review, 2017)
The objectives of this study are; firstly, to examine the effect of profitability on Corporate Social Responsibility (CSR) disclosure; secondly, to examine the effect of leverage on CSR disclosure; thirdly, to examine the effect of company size on CSR disclosure; fourth, to find out whether the effect of leverage on CSR disclosure will be more significant with the inclusion of the variable of majority ownership as moderating variable; fifth, to find out whether the effect of profitability on CSR disclosure will be more significant with the inclusion of the variable of majority ownership as moderating variable. The sample was taken using a purposive sampling technique with 50 manufacturing companies during the period 2011- 2012 which fulfilled the required criteria as the research sample. They were analyzed moderation regression analysis approach. It shows that, first, profitability has positive effect on CSR disclosure; second, leverage has no effect on CSR disclosure; third, company size has an effect on CSR disclosure; fourth, majority ownership moderates the effect of leverage on CSR disclosure; fifth, majority ownership does not moderate the effect of profitability on CSR disclosure. Some limitations stated in this study are expected to be used as references for the improvement of similar studies in the near future.